Thermodynamic and kinetic simulation of Y2O3 and Y2S3 nonmetallic phase formation in liquid steel - Gerasin S.; Kalisz D.; Iwanciw J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The current work deals with the phenomenon of non-metallic inclusions as a result of the addition of yttrium to the liquid steel as an alloying component. The order of introducing individual components determines their final content in steel, and this problem was analyzed using the WYK_Stal program developed at AGH. The study of Y2O3 and Y2S3 phase precipitation and the relationship between the addition of Y, Al, Ca, O, and S in molten steel was studied using the thermodynamic models based on Wagner’s formalism. The introductions of yttrium prior to aluminum brought about huge losses, and it mainly occurred due to the formation of oxides. The low oxygen content in the metal bath promotes the formation of yttrium sulphide. When yttrium is introduced after aluminum and calcium, yttrium is used for the precipitation of its sulfide, and in this way the manganese sulfide formation is reduced.